2018
DOI: 10.1002/btpr.2718
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid production from sugarcane bagasse hydrolysates by Lactobacillus pentosus: Integrating xylose and glucose fermentation

Abstract: Lactic acid, traditionally obtained through fermentation process, presents numerous applications in different industrial segments, including production of biodegradable polylactic acid (PLA). Development of low cost substrate fermentations could improve economic viability of lactic acid production, through the use of agricultural residues as lignocellulosic biomass. Studies regarding the use of sugarcane bagasse hydrolysates for lactic acid production by Lactobacillus spp. are reported. First, five strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 39 publications
2
26
1
1
Order By: Relevance
“…Interestingly, lactic acid has optical isomers: L-lactic acid and D-lactic acid, which can be produced by chemical synthesis (DL-lactic acid) or microbial fermentation (L-lactic acid, D-lactic acid, or DL-lactic acid). Compared to chemical synthesis processes, microbial fermentation processes present more advantages since they make use of renewable substrates from lactic acid bacteria [38]. Consistently, our study demonstrated that fermented rice-acid inoculated with K. marxianus L1-1 could produce more concentration of L-lactic acid in 3 day than 1 day, and the L-lactic acid has some advantages for healthy.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, lactic acid has optical isomers: L-lactic acid and D-lactic acid, which can be produced by chemical synthesis (DL-lactic acid) or microbial fermentation (L-lactic acid, D-lactic acid, or DL-lactic acid). Compared to chemical synthesis processes, microbial fermentation processes present more advantages since they make use of renewable substrates from lactic acid bacteria [38]. Consistently, our study demonstrated that fermented rice-acid inoculated with K. marxianus L1-1 could produce more concentration of L-lactic acid in 3 day than 1 day, and the L-lactic acid has some advantages for healthy.…”
Section: Discussionsupporting
confidence: 79%
“…of productivity). In another study, conducting simultaneous saccharification and co-fermentation (SSCF) with an initial pretreatment of the sugarcane bagasse using L. pentosus showed total consumption of both, xylose and glucose, producing 65.0 g LA•L −1 , and 0.93 g•g −1 of yield, where the productivity reached 1.01 g LA•L −1 •h −1 [3]. In another work, sugarcane bagasse hydrolysate obtained after pretreatment with dilute acid and alkaline was fermented using SHCF process for LA production by Lactobacillus spp, and resulted in a LA production and productivity of 42.5 g LA•L −1 and 1.02 g LA•L −1 •h, respectively.…”
Section: Fermentation Of Sugarcane Biomassmentioning
confidence: 99%
“…The focus nowadays is on the use of different types of treatments used for the transformation of lignocellulosic biomass into suitable substrates for industrial production. Therefore, several methods of fermentations and genetic modifications are underway in order to increase the production and the scale up of LA process [3,12,13]. The biodegradability and biocompatibility of PLA makes the polymer safe and ideal for its application in a wide range of industries, with increased environmental awareness worldwide promoting the development of such technologies for a sustainable approach [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to chemical methods, l‐ lactic acid can be produced by microbial fermentation, which has various advantages, including the absence of racemates and environmental friendliness [7]. The selection of l ‐lactic acid producers is a basic and vital step for laboratory and industrial production.…”
Section: Introductionmentioning
confidence: 99%